3.6k views
2 votes
Solve the equation.

(X-5)(x + 7) = 0
X=
-D
(Use a comma 6 separate answers as needed.)

User BWW
by
5.5k points

1 Answer

2 votes

9514 1404 393

Answer:

x = -7, 5

Explanation:

The equation is written as a product equal to zero. The "zero product rule" tells us that a product is zero if and only if one or more factors are zero. Each factor will be zero when x takes on a value equal to the opposite of the constant in that factor.

x -5 = 0 ⇒ x = 5

x +7 = 0 ⇒ x = -7

The solutions to the equation are x = -7, 5.

User Davemyron
by
6.0k points